Estimates of genetic components of variation in sponge gourd (Luffa cylindrica Roem.) - Kumar, Rajesh; Munshi, AD; Behera, TK; Kumar, Ravinder; Sureja, Amish Kumar (Vegetable Science, 2012)
Sponge gourd (Luffa cylindrica Roem.), also known as dishrag gourd, dishcloth gourd, loofah gourd, and smooth loofah (Whitaker and Davis, 1962), is a popular low cost vegetable in the tropical and subtropical regions. It is an important component of crop rotation during pre-kharif and kharif seasons in North Indian condition and is cultivated both on commercial scale and in kitchen gardens. India is considered as the centre of origin of Luffa species (Choudhury, 1996) and exhibits considerable amount of genetic diversity with respect to different characters. The improvement programme of sponge gourd is based mainly on exploiting natural sources of germplasm by means of selection and hybridization followed by selection.